Nephron-sparing surgery for Wilms tumor - Murphy, Andrew J.; Davidoff, Andrew M. (Frontiers in Pediatrics, 2023)
The algorithm that has been used successfully in the surgical management of unilateral Wilms tumor, radical nephroureterectomy, cannot be used in children who present with synchronous bilateral renal masses. Instead, a surgical approach that removes all tumor masses while preserving as much normal renal parenchyma as possible is encouraged to avoid acute and long-term renal insufficiency. We will review technical aspects of the conduct of nephron-sparing surgery for synchronous bilateral Wilms tumor, including the more recent advances in the use of imaging adjuncts such as pre-operative 3D imaging and fluorescence-guided surgery. The potential role of nephron-sparing surgery for unilateral Wilms tumor will also be discussed.